ANALISIS STRATEGI DINAS PERHUBUNGAN KABUPATEN MUSI RAWAS DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK - Muhammad Effendi; Mariati Mariati (Jurnal Media Ekonomi (JURMEK), 2020)
This study aims to find out how the quality of public services in the Musi Rawas District Transportation Department and to find out what strategies Musi Rawas District Transportation Agency is doing in Improving the Quality of Public Services. This study uses a qualitative research method with a descriptive pattern, intending to systematically describe the facts and characteristics of the object or subject being studied appropriately, namely internal and external factors of the Department of Transportation of Musi Rawas Regency, using SWOT analysis. The process of using a SWOT analysis is done by looking at internal conditions about strengths and weaknesses, as well as external conditions namely opportunities (threats) and thearts (opportunities) of the Department of Transportation, Musi Rawas Regency. The research was conducted through observation, documentation and in-depth interviews with research informants. Determination of priorities and alternative strategies is carried out through the Groub Discution Forum (FGD), the participants of which are research informants, namely officials in the Department of Transportation, Musi Rawas Regency. The FGD participants were also from related stakeholders. From the results of the research and discussion, alternative strategies were recommended to the Musi Rawas District Transportation Office in Improving the Quality of Public Services namely; (1) strategies for increasing human resources, (2) strategies for strengthening regulations, and (3) strategies for improving facilities and infrastructure.